(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the complex issues related to the establishment of a democratic state and an independent economy in the society of Uzbekistan, the elimination of the consequences of the planned administrative system, and the need to transition to market relations. It is also included in the income tax levied on the wages of employees of a class in need of social protection (disabled persons) and certain categories (single mothers with minor children). Ensuring women’s employment did not fail to have an impact on the rapid development of the economy. This will also increase the gross domestic product of the country.